2019
DOI: 10.1177/8755293019878199
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 update of the US National Seismic Hazard Model: Overview of model and implications

Abstract: During 2017–2018, the National Seismic Hazard Model for the conterminous United States was updated as follows: (1) an updated seismicity catalog was incorporated, which includes new earthquakes that occurred from 2013 to 2017; (2) in the central and eastern United States (CEUS), new ground motion models were updated that incorporate updated median estimates, modified assessments of the associated epistemic uncertainties and aleatory variabilities, and new soil amplification factors; (3) in the western United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
212
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(221 citation statements)
references
References 71 publications
3
212
0
Order By: Relevance
“…Chang et al (2006) show that a steeply dipping (55–70°) planar structure is also consistent with geodetic data collected along the Wasatch front. Seismic hazard modeling for northern Utah has largely adopted this structure for the WFZ, employing a dip of 50° ± 15° (Petersen et al, 2019; Wong et al, 2016). Ground motion modeling (Moschetti et al, 2017; Roten et al, 2011) and ShakeMap scenarios (Pankow et al, 2015) of hypothetical M7 earthquakes on the SLCS also use a dip of ~50°.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (2006) show that a steeply dipping (55–70°) planar structure is also consistent with geodetic data collected along the Wasatch front. Seismic hazard modeling for northern Utah has largely adopted this structure for the WFZ, employing a dip of 50° ± 15° (Petersen et al, 2019; Wong et al, 2016). Ground motion modeling (Moschetti et al, 2017; Roten et al, 2011) and ShakeMap scenarios (Pankow et al, 2015) of hypothetical M7 earthquakes on the SLCS also use a dip of ~50°.…”
Section: Introductionmentioning
confidence: 99%
“…Probabilistic seismic hazard analysis (PSHA) depends on the distribution, size, and rate of earthquakes near a given site. For example, the Uniform California Earthquake Rupture Forecast (UCERF) estimates earthquake magnitude rates on California faults for use in PSHA, such as for the National Seismic Hazard Model (e.g., Petersen et al, 2020). A major addition to the third version of the forecast, UCERF3 (Field et al, 2014), is the inclusion of multifault ruptures throughout the state.…”
Section: Introductionmentioning
confidence: 99%
“…[90,91]. This approach is also being adopted by the US IBC [85]. Thus, it is suggested that, for future editions of the AS1170.4, seismic hazard be calculated directly for a given site class using amplification models provided by the developers of each of the GMMs used in the ground-motion logic tree.…”
Section: Site Class Factorsmentioning
confidence: 99%